Retardation of oil cracking to gas and pressure induced combination reactions to account for viscous oil in deep petroleum basins: evidence from oil and n-hexadecane pyrolysis at water pressures up to 900bar - Uguna, Clement N.; Carr, Andrew D.; Snape, Colin E.; Meredith, Will (Elsevier, 2016)
This study reports a laboratory pyrolysis experimental study on oil and n-hexadecane to rationalise the thermal stability of oil in deep petroleum reservoirs. Using a 25 ml Hastelloy pressure vessel, a 35° API North Sea oil (Oseberg) and n-hexadecane (n-C16), were pyrolysed separately under non-hydrous (20 bar), low pressure hydrous (175 bar) and high liquid water pressure (500 and 900 bar) at 350°C for 24 h. This study reports a laboratory pyrolysis experimental study on oil and n-hexadecane to rationalise the thermal stability of oil in deep petroleum reservoirs. Using a 25 ml Hastelloy pressure vessel, a 35° API North Sea oil (Oseberg) and n-hexadecane (n-C16), were pyrolysed separately under non-hydrous (20 bar), low pressure hydrous (175 bar) and high liquid water pressure (500 and 900 bar) at 350 °C for 24 h. This study shows that the initial cracking of oil and n-hexadecane to hydrocarbon gases was retarded in the presence of water (175 bar hydrous conditions) compared to low pressures in the absence of water (non-hydrous conditions). At 900 bar water pressure, the retardation of oil and n-hexadecane cracking was more significant compared to 175 bar hydrous and 500 bar water pressure conditions. Combination reactions have been observed for the first time in pressurised water experiments during the initial stages of cracking, resulting in the increased abundance of heavier n-alkane hydrocarbons (> C20), the amount of unresolved complex material (UCM), as well as the asphaltene content of the oil. These reactions, favoured by increasing water pressure provide a new mechanism for rationalising the thermal stability of oils, and for producing heavy oils at temperatures above which biodegradation can occur. Indeed, we demonstrate that bitumen from the high pressure Gulf of Mexico basin has been formed from lighter oil components and it possesses similar characteristics to the laboratory oils generated.